Issues on the application of IFRS9 and fair value measurement for Islamic financial instruments - Shafii Z.; Abdul Rahman A.R. (Emerald Group Publishing Ltd., 2024)
PurposeThis paper aims to examine some issues in IFRS9 with regards to classification and measurement of Islamic financial assets. In addition, the paper discusses the Shariah concerns on the use of fair value to measure financial assets. Design/methodology/approachThis paper adopts qualitative method via the study of documents and textual analysis of Shariah opinions of scholars and relevant accounting standards. FindingsThe paper found that the classification and measurement of equity-based Islamic financial assets do not fit into the default classification category of amortised cost, as the future cash flow receivable does not constitute solely the payment of principal and interest (fixed rate payment). With regards to fair value measurement, Shariah concern arises during the adoption of fair value at Level 2 (reference of asset values from input other than quoted prices in active markets) and Level 3 (use of discounted cash flow method to arrive to asset valuation) because of the existence of in uncertainty or gharar as compared to Level 1 (fair value referred to quoted prices of similar assets). Practical implicationsFindings of the paper provide a starting point for a debate and extensive research on issues related to classification and measurement of Islamic financial assets and the use of fair value as a method of subsequent revaluation of Islamic financial assets. The Shariah analysis in the paper is useful for International Accounting Standard Board to engage with Islamic financial institutions and local accounting standard setters to reflect the unique nature of Shariah-compliant financial instruments. The paper serves as a basis to devise technical solutions to address accounting and reporting issues of Islamic financial instruments. Originality/valueThe paper offers Shariah analysis on the issue of classification, measurement and impairment model for Islamic financial assets. The paper is considered as the first paper that examines areas of possible tensions when applying IFRS9 to the accounting of Islamic financial assets. In addition, the paper has contributed to the literature in Islamic accounting and auditing. 2016, Emerald Group Publishing Limited.